2019
DOI: 10.1016/j.yclnex.2019.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Sub-chronic administration of brewed coffee on rat behavior and cognition and oxidative stress Alzheimer's disease model

Abstract: neuro-inflammatory response in the hippocampus. Thus, our study further provides evidence for the therapeutic supplementation of BC for various neurodegenerative disorders including AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Accordingly, the investigators observed that the intake of caffeine (1g/L in drinking water two weeks before the STZ challenge) inhibited memory deterioration and neurodegeneration caused by STZ and also A2AR up-regulation (31). Larsson and Orsini showed that there is no association between 1 cup/ day of coffee consumption and the increased risk of overall dementia or AD specifically (32); moderate coffee drinking (3 -5 cups/day) has a protective role in preventing the risk of dementia (14).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Accordingly, the investigators observed that the intake of caffeine (1g/L in drinking water two weeks before the STZ challenge) inhibited memory deterioration and neurodegeneration caused by STZ and also A2AR up-regulation (31). Larsson and Orsini showed that there is no association between 1 cup/ day of coffee consumption and the increased risk of overall dementia or AD specifically (32); moderate coffee drinking (3 -5 cups/day) has a protective role in preventing the risk of dementia (14).…”
Section: Discussionmentioning
confidence: 98%
“…LTP recording was conducted 0.25, 0.5, 1, and 3h after HFS. In order to assess any improvements in the synaptic reaction of the DG, the percent of population spike (PS) amplitude (AMP) and field excitatory postsynaptic potential (fEPSP) slope were measured (13,14).…”
Section: Ltp Recordingmentioning
confidence: 99%
“…No dose-dependent conclusion can be drawn from the changes observed in the 0.29 g/kg BW group, as the highest dose did not exacerbate the parameters measured. Contrarily, the consumption of coffee has been reported to decrease liver enzymes associated with liver damage and has shown protective effects attributed to its polyphenol content [ 38 , 39 , 40 , 41 , 42 , 43 ]. There were favorable significant reductions in liver enzymes (ALP and ALT) and lipid profile indicator (triglyceride) in the low male dose group but no trend was evident in the higher dose groups except in the female triglyceride level when given the high dose.…”
Section: Discussionmentioning
confidence: 99%
“…The fermented coffee extracts are dissolved in Milli-Q water and administered at dose 600 mg / kg I.P for 45 days [22,23]. The twenty-four rats were divided into four groups.…”
Section: Drug and Treatment Schedulementioning
confidence: 99%